Demographic and epidemiological characteristics of COVID-19 epidemic in Albania - Elona Gaxhja; Gjergji Koja; Brunilda Elezi; Elvin Rada; Shkelqim Hidri (Journal of Infection in Developing Countries)
Introduction: This study provides a general overview of the coronavirus disease 2019 (COVID-19) pandemic in Albania. The aim was to assess the spread of COVID-19 in the country by describing the demographic and epidemiological characteristics.